Population structure and physiological plasticity of Favia gravida with differences in terrestrial influence (Ocean and Coastal Research, 2020)
Terrestrial runoff is a source of sediments and nutrients to coral reefs. Due to runoff, Brazilian reefs are typically turbid, and have coral species that are naturally turbidity-resistant. This study investigated how terrestrial input influences population and physiology for the coral Favia gravida on two reefs with differences in river mouth proximity in eastern Brazil. The population structure and physiological traits of F. gravida colonies were assessed on both reefs, then some colonies selected for a subsequent transplantation experiment. The reef less impacted by terrestrial influence showed higher population density and lower recruitment. At this site, the coral colonies displayed higher calcification and larger larvae. The reproductive effort between coral populations at the two sites showed no significant difference. The transplantation experiment confirmed the high physiological plasticity of F. gravida colonies at the more turbid reef site. Despite being regarded as a more challenging environment, where F. gravida has a lower population density, the reef closer to the river mouth appears to secure more nutrients, which may heterotrophically compensate its coral colonies.